P263 Paradoxical embolus causing myocardial infarction in a young adult with congenital heart disease. (17th January 2020) - Veerappan, S; Moharem-Elgamal, S; Luszczak, J; Manghat, N; Lyen, S; Bedair, R
Abstract: Case Report: A 17 year old girl presented to her local hospital 24 hours after the onset of severe central chest pain that lasted for 30 minutes and spontaneously resolved. Her congenital heart disease background was of Ebstein's anomaly of the tricuspid valve, coarctation of the aorta and ventricular septal defect (VSD). She underwent surgical repair of the coarctation and PA band at two months of age, followed by VSD closure when she was a year old.. An atrial communication was deliberately left open at the time of this operation and she had a known residual VSD and mild tricuspid regurgitation. Her resting saturations were 97% in air . On admission, she had a significantly raised Troponin T of 24, 000ng/L with no significant ST segment elevation. An echocardiogram demonstrated new left ventricular (LV) systolic impairment with an ejection fraction of 33%. She underwent a 'triple rule out' cardiac CT scan and subsequently a cardiac MRI. On retrospective review, the CT demonstrated a sizeable atrial communication with left to right shunt, focal tight mid left anterior descending (LAD) artery stenosis aftersecond diagonal branch with mid to apical anterior and anteroseptal hypoperfusion. The MRI demonstrated extensive full thickness late gadolinium enhancement in mid to apical septum extending to the apical cap and apical inferior segment with microvascular obstruction (MVO) in the mid septum with possible VSD patch breakdown. No thrombi was notes on the gadolinium enhancement images. She was transferred to our hospital and underwent an invasive coronary angiogram that demonstrated recanalization of her coronary artery. She remained haemodynamically well throughout the admission. Anticoagulation with a direct acting oral anticoagulant (DOAC) was started alongside ACE-I and Beta blocker therapy. Discharge transthoracic echocardiogram showed flow across the atrial septum, a small residual VSD and mild LV dysfunction with akinesia of mid-to-distal LAD territory and very good function of remaining LV segments. She was discharged home with a plan for elective outpatient admission for a closure of her interatrial communication in a few months once she has recovered. Figure 1 summarises the key aspects of the multimodality imaging in this patient. Discussion: Coronary embolus is the underlying cause of 3% of acute coronary syndromes with a small proportion being from a paradoxical embolus from the venous circulation through a right to left shunt across an atrial communication. Ebstein's anomaly is a rare disorder, accounting for <1% of all congenital heart defects. Right-to-left shunt across the atrial communication is common in this condition due to RA dilatation and increased RA pressures secondary to tricuspid regurgitation. Our case illustrates the importance of having a high index of suspicion in patients with congenital heart disease for this rare complication of paradoxical coronary embolus, especially given the significant morbidity.